Study the structural and optical properties of nanostructure ZnS thin film prepared by Radio frequency (RF) magnetron sputtering technique - Azhar Mohammed Abed; Abdulhussain K. Elttayef; Khalid Hamdi Razeg (Tikrit Journal of Pure Science, 2019)
Zinc sulfide (ZnS) thin films were deposited on glass substrate with different thickness by radiofrequency (RF) magnetron sputtering technique, and deals with effect of thickness on the optical and structural properties. The structure, surface morphology and optical properties are investigated by x-ray diffraction (XRD), atomic forces microscopy (AFM), scanning electron microscopy, and UV-visible spectrophotometer.  The result of XRD show that ZnS thin film exhibited cubic structure with strong peaks at (111) as highly preferential orientation. The maximum particle size of films was found to be 14.4 at thickness 868nm. SEM image show that the shape of grain is like spherical. The result of AFM shows that the surface roughness decrease with increasing in film thickness from (6.19 to 1.45)nm. The result of UV-visible suggests that transmittance increasing with increases in film thickness, the value maximum of ZnS transmission was 87.82%  at thickness 868nm, can be very much useful in the field of solar cell and optical sensor .